Comprehensive immune profiling reveals that Orbivirus infection activates immune checkpoints during acute T cell immunosuppression - Louloudes-Lázaro, Andrés; Rojas, José M.; García-García, Isabel; Rodríguez-Martín, Daniel; Morel, Esther; Martín, Verónica; Sevilla, Noemí (Frontiers in Immunology, 2023)
Bluetongue virus (BTV) is an arbovirus transmitted by the bite of infected Culicoides midges that affects domestic and wild ruminants producing great economic losses. The infection induces an IFN response, followed by an adaptive immune response that is essential in disease clearance. BTV can nonetheless impair IFN and humoral responses. The main goal of this study was to gain a more detailed understanding of BTV pathogenesis and its effects on immune cell populations. To this end, we combined flow cytometry and transcriptomic analyses of several immune cells at different times post-infection (pi). Four sheep were infected with BTV serotype 8 and blood samples collected at days 0, 3, 7 and 15pi to perform transcriptomic analysis of B-cell marker+, CD4+, CD8+, and CD14+ sorted peripheral mononuclear cells. The maximum number of differentially expressed genes occurred at day 7pi, which coincided with the peak of infection. KEGG pathway enrichment analysis indicated that genes belonging to virus sensing and immune response initiation pathways were enriched at day 3 and 7 pi in all 4 cell population analyzed. Transcriptomic analysis also showed that at day 7pi T cell exhaustion pathway was enriched in CD4+ cells, while CD8+ cells downregulated immune response initiation pathways. T cell functional studies demonstrated that BTV produced an acute inhibition of CD4+ and CD8+ T cell activation at the peak of replication. This coincided with PD-L1 upregulation on the surface of CD4+ and CD8+ T cells as well as monocytes. Taken together, these data indicate that BTV could exploit the PD1/PD-L1 immune checkpoint to impair T cell responses. These findings identify several mechanisms in the interaction between host and BTV, which could help develop better tools to combat the disease.